Biosynthesis of Silver Nanoparticles Using Coconut Fiber Extraction and Study of Antimicrobial Effects in Vitro - Nguyen , Thị Hiếu Trang; Nguyen , Thị Thúy Liễu; Le , Sĩ Ngọc; Nguyen , Hoàng Thảo Ly; Pham , Thị Hà Vân; Pham , Quang Thắng (Journal of Technical Education Science, 2018)
The biosynthesis of metal nanoparticles has been proposed as low cost, simple and environmental friendly alternative to chemical and physical methods. Silver nanoparticles was synthesized by biological reduction method using coconut fiber extraction to reduce the silver nitrate solution AgNO3 with concentration of 1, 2.5, 5, 7.5, 10, 15 mM. The shape and structure of the synthesized silver nanoparticles were characterized by ultraviolet–visible Spectrophotometry (UV–Vis), transmission electron microscopy (TEM) and Field Emission Scanning Electron Microscopy (FE – SEM). The results showed that the absorption wavelength of the silver nanoparticle solution was about 450 nm, the size of silver particle is so small (<50 nm). Testing antibacterial, antifungal of the silver nanoparticle solution including Aspergillus niger, Penicillium sp., Erwinia sp. were good antimicrobial efficiency (over 77% at the concentration of 5-7.5 mM AgNO3).